Experimental prescription, rising resistance: the alarming misuse of ceftazidime-avibactam in healthcare systems - Mojtaba Akbari; Christian G Giske; Hamid Solgi (Iranian Journal of Microbiology)
No Abstract No Abstract No Abstract